Biosorption of lead ions from the aqueous solution by Sargassum filipendula: Equilibrium and kinetic studies. Issue 4 (December 2016) - Verma, Ayushi; Kumar, Shashi; Kumar, Surendra
Highlights: Lead removal is studied by abundant and low cost brown alga S. filipendula . Optimization of process variables is carried out by RSM. Experimental data is best fitted by Bangham kinetic model and Fritz isotherm model. Reusability of biosorbent is checked and the process is thermodynamically feasible. Abstract: The removal of Pb +2 ions by Sargassum filipendula was studied using batch process. The biosorbent characterization was carried out by FESEM-EDX and FTIR techniques. Central composite design was used to optimize Pb +2 ions biosorption process by varying four different independent process parameters (temperature, pH, biosorbent dosage, and initial concentration of Pb +2 ions). The adequacy of response surface model was checked by analysis of variance (ANOVA). The optimum process parameters for the removal of Pb +2 ions were found as temperature (34.8 °C), pH (4.99), initial concentration (152.10 mg/L) and biosorbent dosage (0.49 g/L) at which 96% of removal were achieved. The predictive capabilities of six types of kinetic models and six types of adsorption isotherm models were examined for S. filipendula . For this study, Fritz isotherm model and Bangham kinetic model were found as best fitted models for the biosorption of Pb +2 ions. Desorption studies showed that after four consecutive biosorption-desorption cycles 77.53% and 90.84% of desorption and biosorption efficiency were achieved, respectively. The studied thermodynamic parameters showed that biosorption of Pb +2 ions on S. filipendula were feasible, spontaneous, and endothermic in nature. Thus, in view of experimental observations it can be concluded that S. filipendula can be used as an efficient biosorbent for Pb +2 ions biosorption from the aqueous solution.